Comprendre les faibles taux d’adhésion et de cotisation aux mutuelles de santé : exploration dans quatre communes du Bénin - Hervé Bonaventure Mêtonmassé Gbénahou (Anthropologie & Santé)
Given the persistence of low rates of adherence and retention in mutual health insurance, the present anthropological study questions the local knowledge and the practices of populations with regard to disease, health insurance, savings and solidarity. Carried out in four municipalities of Benin’s Zou department, the study reveals first and foremost a divergence between local knowledge on disease and the mutualist principles governing preventive healthcare. It also highlights a striking contrast between local savings practices and the low rates of membership and contributions to healthcare insurance. Finally, it shows complex congruence between solidarity existing in the mutual insurance system and the local practices in the field of solidarity.